Regionalization of neonatal intensive care in Korea - Yun Sil Chang (Korean Pediatric Society, 2011)
In the current era of low-birth rate in Korea, it is important to improve our neonatal intensive care and to establish an integrative system including a regional care network adequate for both high-risk pregnancies and high-risk newborn infants. Therefore, official discussion for nation-wide augmentation, proper leveling, networking, and regionalization of neonatal and perinatal care is urgently needed. In this report, I describe the status of neonatal intensive care in Korea, as well as nationwide flow of transfer of high-risk newborn infants and pregnant women, and present a short review of the regionalization of neonatal and perinatal care in the Unites States and Japan. It is necessary not only to increase the number of neonatal intensive care unit (NICU) beds, medical resources and manpower, but also to create a strong network system with appropriate leveling of NICUs and regionalization. A systematic approach toward perinatal care, that includes both high-risk pregnancies and newborns with continuous support from the government, is also needed, which can be spearheaded through the establishment of an integrative advisory board to propel systematic care forward.